Strategi Bisnis Berkelanjutan Bagi UMKM di Kampong Bharu, Kuala Lumpur - Erna Wigati; Ilham Sentosa; Setiawan Priatmoko; Susilo Budi Winarno (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Digital technology has become an essential part of managing small and medium-sized enterprises (SMEs), especially in efforts to achieve business sustainability. Kampong Bharu, as an iconic area in Kuala Lumpur, is home to numerous micro, small, and medium-sized enterprises (MSMEs) operating in the culinary, craft, and tourism sectors, but faces challenges in implementing environmentally friendly practices. This research aims to analyze the application of green digital management to MSMEs in Kampong Bharu as a sustainable business strategy. The research method uses a qualitative approach with in-depth interviews and participant observation of 15 MSME actors. The research results show that integrating digital technology with environmentally friendly principles, such as paperless digital marketing, energy-efficient use, and sustainable packaging systems, can enhance the competitiveness and positive image transformation of MSMEs. This finding has practical implications for business owners and stakeholders in developing a digital-based green MSME model in historic urban areas. These findings can also serve as a guide for implementing sustainable business strategies in the MSME sector in other major cities.